Spotlight on adolescent health and well-being. Findings from the 2017/2018 Health Behaviour in School-aged Children (HBSC) survey in Europe and Canada. International report. Volume 1. Key findings - (:unkn) unknown (WHO Regional Office for Europe, 2020)
This report presents key findings from 227 441 young people aged 11, 13 and 15 years in 45 countries/regions who participated in the 2017/2018 Health Behaviour in School-aged Children (HBSC) survey. The findings highlight some positive trends in relation to adolescents’ health and well-being. Most adolescents experience positive and supportive social relationships, relatively few health problems, and good overall health and well-being. Substance use continues to decline and eating habits are improving. Challenges nevertheless remain. There is some evidence of increasing pressure at school, especially among older adolescents, at a time when perceived support from family and teachers decreases. The proliferation of digital media has led to problematic use among some adolescents whose social media behaviours affect their relationships with family and friends and disrupt other activities. Physical activity levels remain extremely low and increasing numbers of young people are reporting issues that affect their mental health, such as feeling low and sleep difficulties. Persistent social and gender inequalities remain, and many aspects of health and well-being worsen with age. By helping to make young people’s lives more visible, HBSC continues to underpin effective actions to promote the health of adolescents across the WHO European Region, Canada and beyond.
Keywords: Inclusive Society